2021
DOI: 10.1007/s11427-021-1973-0
|View full text |Cite
|
Sign up to set email alerts
|

MS1 is essential for male fertility by regulating the microsporocyte cell plate expansion in soybean

Abstract: Male sterility is an essential trait in hybrid seed production, especially for monoclinous and autogamous food crops. Soybean male-sterile ms1 mutant has been known for more than 50 years and could be instrumental in making hybrid seeds. However, the gene responsible for the male-sterile phenotype has remained unknown. Here, we report the map-based cloning and characterization of the MS1 gene in soybean. MS1 encodes a kinesin protein and localizes to the nucleus, where it is required for the male meiotic cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
(61 reference statements)
0
26
0
Order By: Relevance
“…Similarly, knockout of GmPRR37 by the CRISPR system suggested that it can repress flowering under LD (Wang et al, 2020c). Two CRISPR/Cas9 gene-editing mutants of Glyma.13G114200 exhibited male sterility phenotype, confirming that it was the casual gene for GmMS1 for male sterility (Fang et al, 2021b;Jiang et al, 2021;Nadeem et al, 2021). CRISPR/Cas9 was also be applied in yield and seed qualityrelated trait modifications, such as to alter plant architecture by editing GmLHYs (Cheng et al, 2019) or SPL9 (Bao et al, 2019;Cai et al, 2018;Cheng et al, 2019), to increase seed number per pod by editing Ln (Cai et al, 2021), to reduce beany flavour by knocking out LOXs (Wang et al, 2020b), to increase isoflavone content by editing GmF3H1, GmF3H2 and GmFNSII-1 simultaneously (Zhang et al, 2020f) and to alter the fatty acid profiling by editing FAD2-2 (Al .…”
Section: Genome Editingmentioning
confidence: 94%
“…Similarly, knockout of GmPRR37 by the CRISPR system suggested that it can repress flowering under LD (Wang et al, 2020c). Two CRISPR/Cas9 gene-editing mutants of Glyma.13G114200 exhibited male sterility phenotype, confirming that it was the casual gene for GmMS1 for male sterility (Fang et al, 2021b;Jiang et al, 2021;Nadeem et al, 2021). CRISPR/Cas9 was also be applied in yield and seed qualityrelated trait modifications, such as to alter plant architecture by editing GmLHYs (Cheng et al, 2019) or SPL9 (Bao et al, 2019;Cai et al, 2018;Cheng et al, 2019), to increase seed number per pod by editing Ln (Cai et al, 2021), to reduce beany flavour by knocking out LOXs (Wang et al, 2020b), to increase isoflavone content by editing GmF3H1, GmF3H2 and GmFNSII-1 simultaneously (Zhang et al, 2020f) and to alter the fatty acid profiling by editing FAD2-2 (Al .…”
Section: Genome Editingmentioning
confidence: 94%
“…Subsequently, the function of MS12 (Glyma.10G117000) was also con rmed by QTL mapping and functional complementation of soybean gene in Arabidopsis cdc20.2 (cell division cycle 20.2) mutant (Zhang 2019). In 2021, both MS1 (Glyma.13G114200) and MS6 (Glyma.13G066600) have been identi ed by ne mapping (Fang, et al 2021;Jiang, et al 2021;Nadeem, et al 2021;). MS6 encodes a Tapetal Development and Functional 1 (TDF1) protein, a R2R3 MYB transcription factor, and predominantly expressed in anther, where it regulated the formation of pollen grain ).…”
Section: Gms System In Soybeanmentioning
confidence: 99%
“…MS6 encodes a Tapetal Development and Functional 1 (TDF1) protein, a R2R3 MYB transcription factor, and predominantly expressed in anther, where it regulated the formation of pollen grain ). Three studies have reported the mapping work of MS1 successively (Fang, et al 2021;Jiang, et al 2021;Nadeem, et al 2021). MS1, encoding a NPK1-ACTIVATING KINESIN 2 (NACK2) protein, participates in regulating cell plate formation after cytokinesis by directly in uencing phragmoplast expansion (Fang, et al 2021).…”
Section: Gms System In Soybeanmentioning
confidence: 99%
See 1 more Smart Citation
“…With the explosion of genomic resources and the rapid development of the third generation hybrid rice technology, more effort has been invested in identifying GMS genes for hybrid breeding in crops. Recently, a few GMS genes have been cloned, namely ms4 (Thu et al, 2019), ms1 (Fang et al, 2021; Jiang et al, 2021; Nadeem et al, 2021), and ms6 (Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%